2020
DOI: 10.1101/2020.06.11.144790
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spectrum of genes for inherited hearing loss in the Israeli Jewish population, including the novel human deafness geneATOH1

Abstract: Variants in more than 150 genes are responsible for inherited hearing loss, with different causal alleles in different populations. The Israeli Jewish population includes communities of diverse geographic origins, revealing a wide range of deafness-associated variants and enabling clinical characterization of the associated phenotypes. Our goal was to identify the genetic causes of inherited hearing loss in this population, and to determine relationships among genotype, phenotype, and ethnicity. Genomic DNA sa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…It is a consensus fact that variants in GJB2 are predominant across all ethnic groups, but there are also some exceptions as shown in Table 1. For example, MYO15A and TMC1 are predominant in consanguineous Egyptian families and Sephardi Jews, respectively (Brownstein et al 2020;Budde et al 2020). This specific causative gene rate is probably the result of consanguineous marriage, which is common in these regions.…”
Section: Responsible Genes In the Japanese Hearing Loss Populationmentioning
confidence: 99%
“…It is a consensus fact that variants in GJB2 are predominant across all ethnic groups, but there are also some exceptions as shown in Table 1. For example, MYO15A and TMC1 are predominant in consanguineous Egyptian families and Sephardi Jews, respectively (Brownstein et al 2020;Budde et al 2020). This specific causative gene rate is probably the result of consanguineous marriage, which is common in these regions.…”
Section: Responsible Genes In the Japanese Hearing Loss Populationmentioning
confidence: 99%
“…Hearing loss affects approximately 466 million people worldwide (Olusanya et al , 2019). A genetic cause can be identified in 60% of the cases of hearing loss in multiplex families, and more than 120 genes have been associated with non‐syndromic hearing loss in humans (Brownstein et al , 2020; Van Camp & Smith, 2020). Although tremendous progress has been made in the understanding of the physiology the auditory system, there are still no biological treatments for hearing loss in humans.…”
Section: Introductionmentioning
confidence: 99%
“…The study reported a C-terminal extension variant (c.1030delC) segregating with hearing loss with onset at birth or early childhood and proposed the impaired degradation of abnormal ATOH1 protein. 18 Although the siblings reported in our study also displayed hearing loss, it is not currently clear whether a similar mechanism of pathogenicity leading to hearing loss could be relevant in the case of biallelic variants.…”
Section: Discussionmentioning
confidence: 60%
“…17 In addition, a recent study reported cosegregation of a heterozygous ATOH1 variant with progressive nonsyndromic hearing loss in a 5-generational pedigree. 18 The ATOH1 gene encodes a 354-amino acid protein that belongs to the bHLH family of transcription factors and is highly expressed during embryonic and early CNS development. The ATOH1 transcription factor is involved in the regulation of neurogenesis in the cerebellum, brainstem, and dorsal spinal cord, maintenance of the intestinal secretory cells, and differentiation of auditory hair cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation